(untitled) (Tribhuvan University Journal of Microbiology, 2024)
Objectives: This study aimed to examine the growth, enzyme activities, and antimicrobial properties of thermophilic bacteria from compost, soil, and hot springs. Methods: Six samples each from compost, soil, and hot springs were collected and thermophiles were isolates. These isolates were tested for growth in extreme conditions (high pH, high salt concentrations, temperature up to 65ºC) and identified by morphological and biochemical characteristics. Enzyme production such as amylase, gelatinase, cellulase, pectinase, and lipase were evaluated, and the antimicrobial properties against test organisms were assessed. Results: From 43 isolates, 17 grew well in high pH, 16 in high salt, and 5 in 65ºC. Bacillus licheniformis had the highest amylase and lipase activity. Bacillus stearothermophilus and Thermoactinomyces had the highest gelatinase activity, Bacillus polymyxa had the highest cellulase activity, and Bacillus macquariensis and Bacillus stearothermophilus had the highest pectinase activity. Antimicrobial activity was observed in 54% of isolates, with 95.7% inhibiting Staphylococcus aureus ATCC 25923, 34.8% inhibiting Escherichia coli, and 1 isolate inhibiting Salmonella spp. Conclusion: The study showed that compost-derived thermophilic isolates had high enzymatic activity. Furthermore, many isolates were able to inhibit the growth of Staphylococcus aureus ATCC 25923 by producing an antimicrobial substance.